Numerical analysis of the influence of in-plane constraints on the crack tip opening displacement for SEN(B) specimens under predominantly plane strain conditions - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a numerical analysis of the relationship between in-plane constraints and the crack tip opening displacement (CTOD) for single-edge notched bend (SEN(B)) specimens under predominantly plane strain conditions. It provides details of the numerical model and discusses the influence of external load and in-plane constraints on the CTOD. The work also reviews methods for determining the CTOD.
Keywords: SEN(B); J-integral; CTOD; Q-stresses; fracture; FEM; coefficient dn